Development of E-Worksheet Oriented Guided Inquiry using Liveworksheet on Electrolyte and Non-Electrolyte Solution Materials - Agustin, Ayu Vina; Sukarmin, Sukarmin (Jurnal Pijar Mipa, 2024)
This research was conducted against the background of the facts in the field that the teaching materials used in learning chemistry use printed LKS / textbooks so that the chemistry learning felt by students is ordinary; the teaching model used is still teacher-centered which causes less active participation of students in learning. It causes the lack of development of critical thinking skills due to the lack of training for students to develop thinking skills. This study aimed to produce guided inquiry-oriented e-worksheets that are feasible as a learning media using live worksheets on electrolyte and non-electrolyte solution material that were reviewed through validity and practicality testing. This research uses the Research and Development (R&D) method based on the Borg and Gall method modified by Sukmadinata until the product trial stage. The product trial was limited to 28 students in class XI at Ta’miriyah Surabaya High School. The novelty of this research is the development of an e-worksheet, which can improve learning outcomes and train critical thinking skills; all 6 indicators of critical thinking skills, according to Facione, with the help of a live worksheet, so it is interactive. This study involved validators, namely 1 person from a chemistry teacher and 2 chemistry lecturer experts, respondents, namely 28 students, and 3 observers. E-worksheet validation results get modes 4 and 5 to be included in the valid and very valid categories. The practical results of the learner response questionnaire get a percentage between 92.86 - 100%, so it is said to be very practical. This is also supported by the learner activity observation sheet, which the observer observes. The research results show that a guided inquiry-oriented e-worksheet using live worksheets can train students’ critical thinking skills on electrolyte and non-electrolyte solution materials.